2017
DOI: 10.1002/jtr.2163
|View full text |Cite
|
Sign up to set email alerts
|

Tourism price causalities: Case of an Adriatic country

Abstract: The aim of this article is to investigate the linearities and causalities between Slovenian tourism and macroeconomic aggregates. The monthly time-series data for the drivers of the rise in the Slovenian hospitality industry prices are tested in the vector autoregressive framework and smooth transition autoregressive model during the 3 specific subperiods. The results are robust for the applied linear methods on prices and value-added tax sensitive tourist demand and for the applied nonlinear methods on exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…where is dependent variable, Π 1 first lagged matrix of observed time-series −1 on lag one, Π 2 second matrix of lag two for observed time-series −2 , Π lagged timeseries matrices, and are unknown parameters as sums of squares of the residuals (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where is dependent variable, Π 1 first lagged matrix of observed time-series −1 on lag one, Π 2 second matrix of lag two for observed time-series −2 , Π lagged timeseries matrices, and are unknown parameters as sums of squares of the residuals (10).…”
Section: Methodsmentioning
confidence: 99%
“…to illustrate the intuition of two autonomous shocks 1 as a real shock causing aggregate supply on institutional policy and 2 causing the low demand tourist services causing aggregate demand (10). The long-term stochastic trend in prices is twice accumulated with shocks, ∑ ∑ 1 , and the cyclical component, , by once accumulated nominal shocks, ∑ 1 , and once accumulated real shocks, ∑ 2 , other intervention dummy variables, , and in (8) the econometric decomposition of the influenced data vector is given (Juselius, 2009…”
Section: Empirical Settingsmentioning
confidence: 99%
“…Comparative research on destination pricing has examined the integration of hospitality pricing in various countries, such as Montenegro and Slovenia (Gričar et al, 2022). In addition, studies have compared hotel room prices between popular destinations in the US and elsewhere (Mathur, 2019) and examined hospitality prices in Slovenia relative to prices in the Eurozone (Gričar & Bojnec, 2018). To further enhance our understanding of destination pricing, research has found spatial price differentiation in tourist attraction tickets in China (Wang, Wu et al, 2021).…”
Section: Research On Price Determinantsmentioning
confidence: 99%
“…According to the actual and credible data sources, CEPOR (2018) and SORS (2018), the number of SMEs and SMEs per capita in Croatia are less than in Slovenia. However, SMEs constitute the most dynamic sector The factors constraining innovation performance of SMEs in Croatia Cahyadin (2017) The relationship between macroeconomic variables and small-andmedium-enterprises in Indonesia de Elejalde, Giuliodori, and Stucchi (2015) Employment and innovation: firm-level evidence from Argentina Gri car and Bojnec (2018) Granger Causalities, Slovenia Gri car et al (2016) Granger Causalities, Slovenia and Montenegro Mahadea and Kaseeram (2018) GDP, unemployment and entrepreneurship Mamman et al (2019) SMEs, GDP growth and unemployment Nelson and Winter (1982) GDP growth theory Poto can and Nedelko (2014) SMEs in Slovenia Ramadani and Dana (2013) Entrepreneurship in the Balkans Viti c and Ringer (2008) Historical path of Slovenia and Croatia of their economies, relative to large enterprises. Generally, the SME sector comprises of relatively younger, more leveraged, more profitable and faster growing enterprises and flexible operations (Klapper, Sarria-Allende, & Sulla, 2002;Sirec & Mo cnik, 2016).…”
Section: Literature Overviewmentioning
confidence: 99%